SCIENCE AND CULTURAL DIPLOMACY IN MULTINATIONAL OPERATIONS - Gruia TIMOFTE (Annals: Series on Military Sciences)
This article presents the main connections between science, culture, diplomacy and politics for using multilateral forces in different alliances, coalitions, or other form of organization, etc., taken in account that every country is keeping total authority over own forces during their mission and taken total authority when the mission is completely accomplished. The principal conclusion is that every country participating with forces in coalitions, alliances, in multilateral operations, etc., must keep the authority and control over own forces in cooperation with all factors with responsibilities in operations.